Pengaruh Struktur Modal Dan Kepemilikan Manajerial Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Pada Perusahaan Manufaktur Sektor Aneka Industri Yang Terdaftar Di Bursa Efek Indonesia Tahun 2019-2023 - ARIFKI FA INDRA Arifki; Yani Suryani; Desi Ika (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to determine the capital structure and managerial ownership of firm value with firm size as a moderating variable in various industrial sector manufacturing companies listed on the Indonesia Stock Exchange in 2019 - 2023.The sample selection method used is purposive sampling. The total observations in this research were 70 observations consisting of 14 companies. The data analysis technique used in this research is moderation analysis using the residual test with the SPSS version 26 analysis tool. The test results of this research indicate that the capital structure proxied as Debt to Equity Ratio and managerial ownership simultaneously or together have an effect on firm value proxied as Price to Book Value. Partially, managerial ownership affects PBV. Meanwhile, DER has no effect on PBV. Company size is able to moderate managerial ownership on PBV, but is unable to moderate the effect of DER on PBV.